Detection of colonisation by extended-spectrum beta-lactamase or carbapenemase producing Enterobacterales from frozen stool specimens - Tan, P; Singh, SR; Mao, B; Evdokimov, K; Saphonn, V; Hsu, LY; Turner, P (BioMed Central, 2020)
Objective To determine the impact of pre-culture ultra-low temperature (ULT, − 80 °C) storage of human stool specimens on recovery of Extended-Spectrum Beta-Lactamase (ESBL) or Carbapenemase (CPM) producing Enterobacterales. Results Twenty stool specimens from a community-based household colonisation study in Cambodia were cultured fresh and after 4–5 days and ~ 6 months of ULT storage (as a slurry in tryptone soya broth–10% glycerol). Presumptive ESBL- and CPM-Escherichia coli isolates were detected in 19/20 (95%) and 1/20 (5%) freshly cultured specimens, respectively. The specimens yielded identical results when re-cultured after ULT storage at both time points. Detection of presumptive ESBL- and CPM-Klebsiella / Enterobacter / Citrobacter group was less frequent and slightly less stable over time. Comparison of antimicrobial susceptibility test profiles between pairs of E. coli and K. pneumoniae isolates from the two frozen culture time points revealed concordance in only 13/28 (46%) pairs, indicating likely colonisation by multiple strains. In conclusion, ULT storage of human stool specimens prior to culture appears to be an acceptable method for managing laboratory workflow in culture-based ESBL / CPM Enterobacterales colonisation studies in high prevalence settings.